2020
DOI: 10.1242/jeb.233197
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal and synaptic polarity of LWamide-like+ ganglion neurons in the sea anemone Nematostella vectensis

Abstract: The centralized nervous systems of bilaterian animals rely on directional signaling facilitated by polarized neurons with specialized axons and dendrites. It is not known whether axo-dendritic polarity is exclusive to bilaterians or was already present in early metazoans. We therefore examined neurite polarity in the starlet sea anemone Nematostella vectensis (Cnidaria). Cnidarians form a sister clade to bilaterians and share many neuronal building blocks characteristic of bilaterians including channels, recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 122 publications
1
6
0
Order By: Relevance
“…In addition, dense-core vesicles at two-way interneuronal synapses and at neuromuscular synapses have been labelled with antibodies against the neuropeptides RFamide and RWamide indicating the involvement of neuropeptides in synaptic signalling. Consistent with bidirectional signalling, at least one neuron type in Nematostella lacks segregated axo-dendritic compartments as suggested by the live imaging of vesicle transport [68]. Both cnidarian and ctenophore inter-neuronal and neuromuscular synapses lack recognizable postsynaptic specializations in electron micrographs (although in the cnidarian Chrysaora postsynaptic cisternae in the muscle have been described [64](Figure 3B).…”
Section: Synaptic Proteins and Synapse Structuresupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, dense-core vesicles at two-way interneuronal synapses and at neuromuscular synapses have been labelled with antibodies against the neuropeptides RFamide and RWamide indicating the involvement of neuropeptides in synaptic signalling. Consistent with bidirectional signalling, at least one neuron type in Nematostella lacks segregated axo-dendritic compartments as suggested by the live imaging of vesicle transport [68]. Both cnidarian and ctenophore inter-neuronal and neuromuscular synapses lack recognizable postsynaptic specializations in electron micrographs (although in the cnidarian Chrysaora postsynaptic cisternae in the muscle have been described [64](Figure 3B).…”
Section: Synaptic Proteins and Synapse Structuresupporting
confidence: 57%
“…Both cnidarian and ctenophore inter-neuronal and neuromuscular synapses lack recognizable postsynaptic specializations in electron micrographs (although in the cnidarian Chrysaora postsynaptic cisternae in the muscle have been described [64](Figure 3B). However, fluorescently tagged Homer and synaptobrevin (putative markers for post and presynapses) showed contact sites between neurites in Nematostella [68]. Consistent with the role of Homer in postsynaptic sites, another study found Homer puncta in transgenic Nematostella at tentacle-retractor and mesentery-retractor muscles and Homer co-expressed with Shank and iGluRs in muscle-cell transcriptomes [69].…”
Section: Synaptic Proteins and Synapse Structurementioning
confidence: 75%
“…35 homologs of voltage-gated potassium channels, 40 two voltage-gated sodium channels, 41 and the voltage-gated calcium channel MleCav2, 42 as well as several homologs of ionotropic glutamate receptors 15,39 and other ion channels, Na/Ca exchanger, a sodium/potassium transporting ATPase, and two innexins are either overexpressed or detectable in the C33 metacell (Table 1; Data S2D). The C33 metacell also expressed structural components defining neuron morphology: [43][44][45] three enriched tubulin genes; the F-actin binding protein dematin; the actin cytoskeleton organizer ABLIM3; contactin 5 and contactin protein-like 2; as well as genes described by ''actin binding'' and ''tubulin binding'' Gene Ontology (GO) terms (Data S2E and S2F). Thus, the expression of multiple genes important for neuronal functions further confirmed that C33 is a neuronal metacell.…”
Section: Newly Identified Putative Neuropeptides Affect Ctenophore Swimming Behaviormentioning
confidence: 99%
“…We will need to learn more about synapses and transmitters in cnidarians. New transgenic approaches [ 137 , 138 ] and serial EM could help to address this.…”
Section: Testable Predictions Of the Hypothesismentioning
confidence: 99%